Inspection of the facades of the Sergadas Vianna and SulAmérica Buildings in Recife/PE using a Remotely Piloted Aircraft to detect pathological manifestations - Albuquerque , Everson Silva de; Anjos , Ana Beatriz Santiago dos; Trajano , Laís Barreto Romão; Monteiro , Eliana Cristina Barreto; Silva , Paula Maciel (Technical and Scientific Journal Green Cities, 2024)
This article presents inspection of facades in two buildings: Sergadas Vianna and SulAmérica. Both buildings are located in the São José neighborhood, in Recife/PE, within the perimeter of one of the Historic and Cultural Preservation Zones in the city center and are representative examples of modern architecture. The present facades were investigated using a Remotely Piloted Aircraft (ARP), carrying out data surveys and preparing damage maps, showing the presence of dirt, concrete spalling, paint detachment, as well as exposed armor with corrosion. The aim of the article is to develop a method for the accurate identification and diagnosis of these pathological manifestations, providing a solid basis for structural maintenance and rehabilitation. The results obtained with the use of ARP facilitated and accelerated the mapping of facades, being precise in identifying each type of pathological manifestation, which provides a comprehensive view of the conditions of the buildings, facilitating informed decision-making for maintenance and repair interventions. The application of these innovative approaches in the field of civil engineering promotes efficiency in the management of urban and historic buildings, contributing to durability, safety, long-term preservation and analysis of the impact of the building’s state of degradation on the integrity of the asset as a property that has cultural value.